Los valores para el fortalecimiento de la identidad cultural en la escuela - Jaque Aimacaña, Katerin Liseth (2023)
This research describes the importance of promoting values at school to strengthen cultural identity in such a way that students accept themselves and join in the interaction with their classmates for a better coexistence. The objective of this research is to promote values for the strengthening of cultural identity in students of the fourth grades of parallel "A" and "B" of the School of Basic Education "Isidro Ayora" Cotopaxi Province, Latacunga Canton, La Matriz Parish, during the school year 2022 - 2023. The methodology was based on the mixed approach (qualitative and quantitative) jointly using the scientific method and the empirical method since they start from a problem to consolidate its verification through scientific questions. Likewise, the type of research is bibliographic, field, non-experimental, and descriptive. On the other hand, for the study of the variables, instruments such as the interview and the survey guide were used, which were directed to the authorities, teachers, and students of the fourth year of primary education, parallel "A" and "B"; and then they were analyzed and interpreted. The results show that all of them do not put into practice the values of cultural identity because they do not carry out constant planning to generate inclusion in students from other cultures. Concerning the research project, the proposal is based on workshop activities to encourage students about the values of cultural identity and, finally, to issue conclusions and recommendations.